Contrastive Analysis of the English and the Igbo Verbal Systems - Nwosu-Okoli, Ifeoma (West African Journal of Open and Flexible Learning, 2026)
Language is properly used when a speaker is able to make accessible to his audience meaningful information on a subject of discourse. To enhance the effectiveness of language, we employ and deploy words and symbols in a manner that is capable of rendering our mental and material constructs intelligible to our audience. In some cases, there are communication breakdown syndromes among language users. Such syndromes are known to occur because of a noted inverse relationship between the intended and the interpreted meanings of works and symbols in use. This experience is very common with second language (L2) learners. With the English language as the medium of communication commonly in use inside (and even outside) the country, it becomes necessary for the serious-minded teacher (who is result-oriented) to devise strategies for discovering and anticipating modes of errors in L2 learning as well as adequate measures for countering such errors.